Dehydrated cane juice in meat quail feed - Santos, Renato Andrade dos; Teixeira, Elisanie Neiva Magalhães; Souza, Janete Gouveia de; Moreira, José Aparecido; Arruda, Alex Martins Varela de; Bezerra, Roseane Madeira; Goulart, Cláudia de Castro (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of dehydrated cane juice (DCJ) on the performance, carcass quality, and economic index of European quails (Coturnix coturnix), during the period from 22 to 42 days of age. One hundred and ninety‑two quails with 22 days of age were distributed in a completely randomized design, with four treatments and six replicates of eight birds each. DCJ was added at 0, 1.5, 3.0, and 4.5% in the feed. The economic feasibility of including DCJ levels in the feed was evaluated through relative gross margin. In the period from 29 to 35 days of age, there was increased linear effect of feed intake with the increase of DCJ in the feed. However, there was a quadratic effect of DCJ levels on carcass, drumstick+thigh, and abdominal fat weights, and the estimated optimum levels were 1.69, 2.50, and 2.34%, respectively. There was a decreasing linear effect of DCJ levels on breast weight with and without skin. Economic analysis showed higher profits to the producer with the use of conventional feed. However, among the DCJ levels of inclusion, the level of 1.5% showed the best results, with a difference of 0.47% in relative gross margin when compared to the conventional feed. The addition of 1.69 and 2.50% of dehydrated cane juice in the feed is recommended to achieve higher carcass and drumstick+thigh weights in meat quails, respectively.